Phenotypic Heterogeneity of Hemostasis in Severe Hemophilia - Nogami, Keiji; Shima, Midori (Seminars in Thrombosis and Hemostasis, 2015)
A reduction in bleeding pattern and arthropathy appears to be observed in approximately 10% of the patients with severe hemophilia (< 1% clotting factor activity). These patients rarely bleed and do not always need prophylactic therapy of therapeutic products, resulting in the wide range of joint damage seen in patients with severe hemophilia. The cause(s) of this phenotypic heterogeneity has been investigated in many studies till date, but remains to be completely solved. The large heterogeneity of the clinical phenotype in severe hemophilia seems to be multifactorial, including variation in the levels of various procoagulant and anticoagulant factors, the balance between the coagulation and fibrinolysis systems, pharmacokinetics of therapeutic products, environmental factors including lifestyle activity, and the limitation of measurement at lower levels of clotting factors. As an approach toward clarification, studies should be designed to evaluate a homogenous cohort of hemophilic A patients with an intron 22 inversion who produce no factor VIII. In the future, by a combination of the measurement of lower levels of clotting factors and the evaluation of global clotting function, it might be possible to better grasp the potential of hemostatic coagulation in individual hemophilia patients, which should in turn be useful for the prediction of bleeding phenotype and the designation of adequate and long-term hemostatic management throughout their life.
Keywords: clinical phenotype; severe hemophilia; heterogeneity